2020
DOI: 10.1038/s41598-020-61651-6
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, partition and environmental risk assessment of per- and polyfluoroalkyl substances in water and sediment from the Baiyangdian Lake, China

Abstract: This work examined the contamination of poly-and perfluorinated compounds (PFASs) in the water and sediment of the Baiyangdian Lake. The total concentration of PFASs in the surface water varied from 140.5 to 1828.5 ng/L, and the highest concentration of PFASs were observed near the entrance of Fuhe river. The topmost contaminant was sodium perfluorohexanesulfonate (PFHxS) and perfluorooctanoic acid (PFOA) in the north and south of the Baiyangdian Lake respectively, which indicated different contamination sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In case of missing research data, the coefficient parameter K d was estimated by multiplying the fraction of organic carbon (f oc [%]) in the sediment samples and the organic carbon partitioning coefficient (K oc ) [ 57 , 58 ]. The K oc data were obtained using the EPI (Estimation Programs Interface) Suite™ software by the U.S. Environmental Protection Agency [ 59 ] (see Table S4 in Supplementary Materials [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]).…”
Section: Methodsmentioning
confidence: 99%
“…In case of missing research data, the coefficient parameter K d was estimated by multiplying the fraction of organic carbon (f oc [%]) in the sediment samples and the organic carbon partitioning coefficient (K oc ) [ 57 , 58 ]. The K oc data were obtained using the EPI (Estimation Programs Interface) Suite™ software by the U.S. Environmental Protection Agency [ 59 ] (see Table S4 in Supplementary Materials [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of PFASs was 50.03-162.26 ng/g•dw with a mean of 131.44 ng/ g•dw in downstream of the water supply river. Comparison with literature showed that the observed PFAS concentration in downstream was much higher than the ΣPFASs of the Songhua River (0.143-1.41 ng/g•dw), the Baiyangdian Lake (0.48-30 ng/g•dw), the southern Beaulieu River (0.2-5.3 ng/ g•dw), the Danjiangkou Reservoir (0.07-1.62 ng/g•dw), and the Taihu Lake (1.11-8.21 ng/g•dw) (Guo et al, 2015;Guo et al, 2020;Li et al, 2020b;Celis-Hernandez et al, 2021). Besides, the sediment concentration of PFBA was at a high level compared with the situations of other parts of the world.…”
Section: Concentration and Composition Of Per-and Polyfluoroalkyl Substances In Sedimentmentioning
confidence: 99%
“…As the largest natural freshwater wetland in a semi-humid zone, Lake Baiyangdian (LBYD) played an important role in maintaining the regional ecosystem cycle and balance, such as that pertaining to water regulation and supply [21,22]. LBYD was once known as the "Pearl of North China" and the "Kidney of North China" [23,24]. However, owing to both natural conditions and the increase in human activities in recent decades, the lake has experienced wetland shrinkage, water scarcity, and water quality deterioration [21,25].…”
Section: Introductionmentioning
confidence: 99%